"And I slip into it unawares": The function of bilingualism in Kobina Sekyi's The Blinkards (1915) - Nasseh, G (Indiana University Press, 2020)
In this essay, I discuss the function of bilingualism in Kobina Sekyi’s The Blinkards (1915). The play, written in both English and Fanti, satirizes the Anglophile tendencies of the Cape Coast’s indigenous bourgeoisie, and extant criticism has tended to focus on the comedic effect of this class’s use and misuse of English. In this article, however, I argue that the bilingual nature of The Blinkards—and, indeed, the linguistic strategies that characterize such bilingualism (i.e., code-switching, indigenization, etc.)—performs, in the context of Sekyi’s nationalism, a profoundly glottopolitical function. Furthermore, I argue that The Blinkards serves to demonstrate the ways in which multilingual colonial and postcolonial works can help to redress the Eurocentric tendencies of contemporary critical debates as to mono- and multilingual practices in a globalized world.